Strategi Promosi Kesehatan dalam Mencegah Stunting - Dyah Ayu Puspa Mawar Indah; Bernabas Benat; Edom Rudianto Ottu; Antonia Helena Hamu; Lisa Amelia (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the variations in health promotion strategies used in preventing stunting cases. The research design method used is qualitative, based on articles and journals published between 2020-2025, accessed through the Google Scholar portal, and employing the PRISMA technique. The results of this study show that advocacy for stunting prevention has already been carried out by health center officers to local government authorities such as village heads, sub-district officials, and relevant regional government organizations (OPD) to obtain budget support and policy backing. Social support is provided in the form of counseling by religious leaders, and family support influences the behavior of providing specific nutritional interventions. Community empowerment is carried out using various models, including the empowerment of health cadres, PKK groups, women, families, and the broader community. Most empowerment efforts increase respondents' knowledge in stunting prevention. The conclusion is that the health promotion strategies found in the literature review are mostly conceptual strategies rather than operational strategies, and do not show whether these strategies are effective in preventing stunting.   Keywords: Advocacy, Community Development, Community Empowerment, Stunting